2009
DOI: 10.1097/ta.0b013e31819db092
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Conservatively Managed Displaced Acetabular Fractures

Abstract: Acetabular fractures involving the weight-bearing dome if reduced by closed means can be maintained by heavy lateral and longitudinal traction resulting in good clinicoradiologic outcome comparable with operative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 13 publications
4
35
0
Order By: Relevance
“…Sen et al reported on a subgroup of 14 patients with acetabular fractures displaced greater than 20 mm who were treated nonoperativley. 17 Reducibility was very poor, as only 2 (14.3%) of the 14 achieved good reduction on follow-up x-ray imaging. It should be recognized, however, that due to the decreased functional demands in the elderly individuals, that which may be considered to be an unsatisfactory result for articular reduction in a younger active patient, may yield a quite satisfactory functional result for an older patient.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Sen et al reported on a subgroup of 14 patients with acetabular fractures displaced greater than 20 mm who were treated nonoperativley. 17 Reducibility was very poor, as only 2 (14.3%) of the 14 achieved good reduction on follow-up x-ray imaging. It should be recognized, however, that due to the decreased functional demands in the elderly individuals, that which may be considered to be an unsatisfactory result for articular reduction in a younger active patient, may yield a quite satisfactory functional result for an older patient.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…A retrospective review by Heffernan et al compared 2194 geriatric patients (>65) versus 2081 younger patients (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) who presented after blunt trauma with similar ISS scores. 24 In this study, mortality increased considerably in the elderly patients with heart rates greater than 90 beats/ min, and systolic blood pressure greater than 100 mm Hg, while similar increases in mortality were not seen in the younger patients.…”
Section: Perioperative Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported incidence of avascular necrosis (AVN) of femoral head following surgically managed acetabular fractures varies between 5.7 % and 30 % during followup periods that have ranged from six to 11.3 years [1][2][3][4][5]. AVN has been reported (two out of 35 patients) even following conservative management of displaced acetabular fractures using skeletal traction [6]. Delayed reduction of the fracturedislocations and severe osteochondral injuries to the acetabulum have been found to be associated with very high (30 %) incidence of AVN [4].…”
Section: Introductionmentioning
confidence: 99%